Hyaluronic Acid-Based Medical Device for Treatment of Alveolar Osteitis-Clinical Study - Suchánek, Jakub; Ivančaková, Romana Koberová; Mottl, Radovan; Browne, Klára Zoe; Pilneyová, Kristýna Charlotte; Pilbauerová, Nela; Schmidt, Jan; Suchánková Kleplová, Tereza (International journal of environmental research and public health, 2019)
Alveolar Osteitis (AO) is a complication following the extraction of a tooth. AO manifests through localized pain in, and around, the extraction site, where the post-operative blood clot has been disintegrated. The aim of this single cohort study was to evaluate the outcome of a treatment of AO, using a pharmacological device composed of hyaluronic acid and octenidine dihydrochloride. The tested device is a sponge-like material, composed solely of a fully dissoluble medicaments (hyaluronic acid, calcium chloride, and octenidine dihydrochloride). It was designed to serve as a non-toxic, slow-dissolving antiseptic, that adheres to mucosa and obturates the wound. This study includes 58 subjects who were diagnosed with AO. The tested device was administered once daily until local pain subsided to < 20 mm of the Visual Analog Scale (VAS). The treatment was considered effective when the pain subsided to < 20 mm VAS in < 8 days of treatment; as per comparative studies. Our findings provide a statistically significant success rate of 96.0% (95.0% confidence interval of 75.75% to 97.8%) after pharmacological device administrations. No adverse medical effects were detected. Acquired data confirmed that lyophilized hyaluronic acid, combined with octenidine, is effective for the treatment of AO. The results are clinically important as AO is a common complication after third molar extractions.
Keywords: Female; lidé středního věku; vstřebatelné implantáty; Absorbable Implants; extrakce zubů; first-in-man study; alveolitis sicca dolorosa; sodium hyaluronate; Dry Socket; octenidine dihydrochloride; mužské pohlaví; kohortové studie; Humans; pyridiny; dospělí; iminy; Tooth Extraction; Pyridines; Anti-Infective Agents, Local; Hyaluronic Acid; lidé; Middle Aged; clinical study; Cohort Studies; alveolalgia; ženské pohlaví; Imines; antiinfekční látky lokální; Adult; alveolar osteitis; Male; poextrakční zánět zubního lůžka; kyselina hyaluronová